2004
DOI: 10.1016/j.ydbio.2003.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Snail family members and cell survival in physiological and pathological cleft palates

Abstract: Palate fusion is a complex process that involves the coordination of a series of cellular changes including cell death and epithelial to mesenchymal transition (EMT). Since members of the Snail family of zinc-finger regulators are involved in both triggering of the EMT and cell survival, we decided to study their putative role in palatal fusion. Furthermore, Snail genes are induced by transforming growth factor beta gene (TGF-beta) superfamily members, and TGF-beta(3) null mutant mice (TGF-beta(3)-/-) show a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
1
6

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(111 citation statements)
references
References 51 publications
6
98
1
6
Order By: Relevance
“…Snail and Twist have been implicated in this fusion process and our data, that Snail and Twist are intensely expressed in the palatal mesenchyme adjacent to the MEE immediately before and during the fusion process, would support this implication (Bloch-Zupan et al, 2001;Martinez-Alvarez et al, 2004). Snail, the closely related Slug and Twist are all known to induce EMT at many sites during development and invasive tumorigenesis (Nieto, 2002;Yang et al, 2004).…”
Section: Twist Snail and Id1 May Have Multiple Roles During Palate supporting
confidence: 58%
See 1 more Smart Citation
“…Snail and Twist have been implicated in this fusion process and our data, that Snail and Twist are intensely expressed in the palatal mesenchyme adjacent to the MEE immediately before and during the fusion process, would support this implication (Bloch-Zupan et al, 2001;Martinez-Alvarez et al, 2004). Snail, the closely related Slug and Twist are all known to induce EMT at many sites during development and invasive tumorigenesis (Nieto, 2002;Yang et al, 2004).…”
Section: Twist Snail and Id1 May Have Multiple Roles During Palate supporting
confidence: 58%
“…Snail proteins induce during mesoderm specification and emergence of neural crest from the neural tube. Snail may also play a role in EMT during fusion of the palatal shelves (Martinez-Alvarez et al, 2004). Twist has also been associated with EMT (Yang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, inappropriate culture conditions are responsible for much of the reported basal cell death (Takigawa and Shiota, 2004). Palates express Snail (Martinez- Alvarez et al, 2004), which promotes cell survival, as well as EMT (Vega et al, 2004). Both the lip and palate midline epithelial seams transform into typical mesenchymal cells (Fig.…”
Section: Significant Emt Centers In the Embryo And The Fate Of The Mementioning
confidence: 99%
“…There is strong evidence that disruption of the palatal epithelial seam during palatal fusion results at least in part from apoptosis (Cecconi et al, 1998;Cuervo and Covarrubias, 2004;Martinez-Alvarez et al, 2004;Vaziri Sani et al, 2005). We carried out terminal deoxynucleotidyl transferasemediated deoxyuridinetriphosphate nick end-labeling (TUNEL) analysis to investigate the mechanism involved in the disruption of the epithelial seam between the palate and tongue in the Jag2 ⌬DSL/⌬DSL mutants and found that the palate-tongue seam contained numerous apoptotic cells, similar to the wild-type palate-palate seam during palatal fusion (Fig.…”
Section: Analysis Of Jag2 Mutants Provides Support For the Role Of Tgmentioning
confidence: 99%